Abdulvehhâb Azzâm'ın seyahatnâmesi Er-Rİhlât’ın ana temaları - Al-Soufi, Ayşe Sadiye (My University, 2023)
ÖZET ABDULVEHHÂB AZZÂM'IN SEYAHATNÂMESİ ER-RIHLÂT’IN ANA TEMALARI Seyyahların, ilim adamlarının, siyasîlerin gezip gördükleri yerleri belli bir estetik kaygı ve üslup çerçevesinde kaleme aldıkları seyahatnâme türü, hem sıradan okuyucular hem de tarih, edebiyat, sosyoloji araştırmacıları için içerdiği bilgilerden dolayı kıymetli kaynaktır. Farklı coğrafyaların iklimleri, toplumsal yapıları, ekonomik şartları, tarihî ve doğal güzellikleri hakkında bilgi verirken; içerdiği anı, hikaye, şiir, mesel gibi edebî unsurlarla da zengin bir anlatım sunar. Doğu ve Batı edebiyatlarında yüzyıllarca ilgi gören bu tür, 20. yüzyılda seyahat şartlarının kolaylaşmasıyla pek çok örneğini vermiştir. Bu tez çalışması, Mısır’ın 20. yüzyılda önde gelen Doğu dilleri âlimi ve devlet adamı Abdulvehhâb Azzâm’ın özellikle İslâm topraklarını içeren iki ciltlik er-Rıhlât isimli seyahatnâmesini incelemeyi ve ana temalarını ortaya çıkarmayı amaçlamıştır. Müellif eserinde tarihe, dile, İslâm toplumlarına dair çeşitli konulara değinmiş, Müslümanlara bazı mesajlar verme kaygısı gütmüştür. Ayrıca yaşadığı döneme ve ziyaret ettiği mekanlara ait verdiği bilgilerle de tarihe not düşmüştür. Onun bu eseri kaleme alırken ana hedefi Müslümanlara birbirlerini tanıtmak ve işgal altındaki İslâm ülkelerinin kendilerini sömürmek isteyen Batılı devletlere karşı birlikte hareket etmelerine katkıda bulunmaktır. Ayrıca eser içerdiği anı, şiir, hikaye gibi özelliklerle de edebî bir zenginliğe sahiptir.

MAIN THEMES OF ABDULWAHHAB AZZAM'S TRAVEL BOOK, ER-RIHLAT The works written by travelers, scholars, and politicians about the places they have visited, with an aesthetic concern and style, are called travel books. Travel books are rich sources for both ordinary readers and researchers in the fields of history, literature, and sociology. They provide information about the climates, social structures, economic conditions, and historical and natural beauties of different geographical regions. They include literary elements such as memoirs, stories, poems, and proverbs, thus offering a rich narrative to the readers. This literary genre has been of interest in both Eastern and Western literature for centuries. The travel book genre has presented numerous examples with the facilitation of travel conditions in the 20th century. In this thesis, the work er-Rihlat by Abdulvehhâb Azzâm, a prominent Eastern languages scholar and statesman of Egypt in the 20th century, will be examined, and the main themes will be identified. The work encompasses Islamic lands and consists of two volumes. The author touches upon various subjects related to history, language, and Islamic societies in his work. He has a concern to convey certain messages to Muslims. Additionally, the work contains historical information through the details provided about the period and locations. The main objective of the author in writing this work is to introduce Muslims to each other and contribute to the idea of collective action against Western states seeking to exploit the occupied Islamic countries. Furthermore, the work possesses literary richness through its inclusion of memoirs, poetry, and stories.
Main themes of Abdulwahhab Azzam's travel book, Er-Rihlat
Keywords: Abdulvehhâb Azzâm; Abdurrahmân b. Hasen b. Sâlim b. Azzâm (1894-1976). Er-Rİhlât; Arabic language; Arabic literature; Arap dili; Arap edebiyatı; AvrupaAbdulwahhab Azzam; edebiyat; Egypt; er-Rihlat; Europe; Hindistan; History and criticism; India; Irak; Iran; Iraq; İran; ittihad-ı İslâm; literature; Mısır; poetry; seyahatnâme; Sham; Şam; şiir; Tarih ve eleştiri; travel book; Turkey; Türkiye; unity of Islam